PENERAPAN PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION UNTUK MENINGKATKAN PEMAHAMAN BERHITUNG SISWA KELAS I SD NEGERI 2 REJOYOSO - ulfatul laila ulfa (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
This study aims to improve Comprehension Comprehension using Realistic Mathematics Education learning models for first-grade students of SD Negeri 2 Rejoyoso Academic Year 2018/2019. This type of research uses Classroom Action Research, through several stages, namely: 1) planning 2) implementation 3) observation and 4) reflection. Data collection techniques were carried out using observation, interviews, tests, and field notes. Data analysis techniques used qualitative. This research was carried out in two cycles consisting of 4 meetings, the learning outcomes obtained in the first cycle of the first meeting averaged 74, 75 % of all students, the second meeting of the first cycle average value of 79.68% of all students and student learning outcomes in the second cycle of the first meeting got an average value of 82.11% of all students, the second meeting received an average value of 90, 58% of all students. Based on the research results of the Realistic Mathematics Education teaching model in Mathematics learning can improve the learning outcomes of students of class I of SD Negeri 2 Rejoyoso.